If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3x = (-1x) + 1 + 2x Reorder the terms: 9 + -3x = 1 + (-1x) + 2x Combine like terms: (-1x) + 2x = 1x 9 + -3x = 1 + 1x Solving 9 + -3x = 1 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + -3x + -1x = 1 + 1x + -1x Combine like terms: -3x + -1x = -4x 9 + -4x = 1 + 1x + -1x Combine like terms: 1x + -1x = 0 9 + -4x = 1 + 0 9 + -4x = 1 Add '-9' to each side of the equation. 9 + -9 + -4x = 1 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 1 + -9 -4x = 1 + -9 Combine like terms: 1 + -9 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 5.3x+100=28.09+10x | | 2x+3-6=x+8-7x | | 29+4a=7(a+2) | | 4x^2-12x-7=9 | | 16=2/5c | | 7(y-4)/4=2y-4 | | 4+2t-3=8t+19-4t | | 19-13w= | | c=.2x^2-98x+12590 | | 7z-(3z-3)=3+2z | | 5x(2y)=435 | | 10(t-2)+8t=6(3t+4)-13 | | -5x-1=x+7 | | 4x-3(1-x)=-15+5x | | -2x+7(3x-1)=32 | | 30kx-6kx=8forx | | f(x)=2x+11-3 | | 5x-15=11+3x | | 4b+2=27 | | 9x-21=15+11x | | 15x=87 | | x-2.97=5.9 | | 5(2x-3)-3(x-7)=5 | | 2x+3=8x-1+6 | | .04(8x-3)=.32(x+7)-2.36 | | 3=6(x-1)+y | | 8x^2=26 | | -7=6w | | 16c^3-2=0 | | -8=9t | | 4+5x=x-125 | | 10x+-1x+8=-10 |